Adsorption Isothermal Methane Gas With Mass Flow Rate of 10 SLPMand 20 SLPM For Adsorbed Natural Gas Storage - Irfandi Pratama; Awaludin Martin; Nasruddin Nasruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The increase energy needs along with the times resulted in the availability of energy derived from fossil fuels thinning. Utilization of natural gas as a potential replacement for fossil fuels because of national gas production shows increase.Natural gas as a  replacement for fossil fuels constrained in the storage process,  storageis oftenusediscompressed  natural  gas(CNG) andliquefied naturalgas(LNG). CNG storage constrained at high pressure (20 MPa) and LNG constrained in gas liquefaction process that requires  extremely low temperatures     (-161.5°C).Adsorbed natural gas (ANG) is a solution to reduce the pressure in the tube of about 3,5 to 4 MPa by utilizing the process of adsorption using activated carbon.Adsorptionmeasurement use volumetric method (isothermal) at temperatures  25oC with 10 bar pressureand variation of the mass flow rate (10 standard liter per minute and 20 standard liter per minute).The purpose of this study was to obtain data of methane (CH4)  stored and out (stuck) on the storage and also to  see temperature phenomena that occur in storage.From the test results,  the massof methane storedat10SLPMis33,19gram and20SLPMis43,63gram.As for themethanegasthat isstuckat10slpm is7,09gramand20slpmis16,54369gram. Keywords:Adsorbed Natural Gas, Volumetric methode , Adsorption Isothermal